1999
DOI: 10.1002/(sici)1099-0690(199902)1999:2<463::aid-ejoc463>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Intramolecular meta Photocycloaddition of Side-Chain-Substituted 5-(2-Methoxyphenyl)pent-1-enes

Abstract: Irradiation of a series of 5‐(2‐methoxyphenyl)pent‐1‐enes substituted with a hydroxy or trimethylsilyloxy group at the α‐, β‐, or γ‐position of the side‐chain yields in all cases meta photocycloadducts, in which the configuration at the substituted carbon atom is mainly endo. This indicates that the diastereoselectivity originates from minimization of steric interactions between the side‐chain substituent and the ortho‐methoxy group at the arene unit. Hydrogen bonding does not seem to be involved. The introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Scheme 1.8: Bryce-Smith"s advocated biradical species, called a "prefulvene" 33, the precedent species to benzvalene (34), the meta photoadduct (35) and fulvene (36).…”
Section: 23mentioning
confidence: 99%
See 4 more Smart Citations
“…Scheme 1.8: Bryce-Smith"s advocated biradical species, called a "prefulvene" 33, the precedent species to benzvalene (34), the meta photoadduct (35) and fulvene (36).…”
Section: 23mentioning
confidence: 99%
“…A further illustration of this was conducted by Jan Cornelisse et al 35 in his studies toward "diastereoselective control of intramolecular meta photocycloadditions of side-chain-substituted 5-(2-methoxyphenyl)-pent-1-enes". They also reported that when there is an -substituent attached to the side-chain, the stereochemistry at that centre results in stereoselectivity in the photoadduct, such that the endo varieties (66 and 67) are predominant (Scheme 1.1.5).…”
Section: 32mentioning
confidence: 99%
See 3 more Smart Citations